Implementation of PZEM-004T and LoRa for Internet of Things–Based Monitoring of Power Supply Sources in Laboratory Building - Sirait, Regina; Pardede, Morlan; Hutajulu, Elferida; Junaidi, Junaidi; Pardede, Stephanie Ch Y; Pakpahan, Arnold (Institute of Computer Science (IOCS), 2025)
This research develops an Internet of Things (IoT)-based system to monitor electrical voltage parameters in two rooms of the Telecommunication Laboratory at Medan State Polytechnic. The system employs two sensor nodes (PZEM-004T, ESP32, and LoRa SX1276) and a gateway node integrated with WiFi and the Blynk cloud. The sensors measure voltage, current, power, energy consumption, frequency, and power factor, which are processed by ESP32 and transmitted via a LoRa multi-point network to the gateway for online monitoring. An automatic cut-off mechanism and email notifications are provided when abnormal voltage or current conditions occur. Experimental results show high measurement accuracy with a maximum error of 0.29% for voltage and 2.52% for current. However, data transmission experienced 20% packet loss, with an average delay of 11 seconds on Blynk and 37 seconds for email notifications. These findings indicate that the proposed system is effective in protecting laboratory equipment from abnormal power sources and provides reliable online and offline monitoring, although transmission performance requires further optimization.